Increase of accuracy of definition of temperature by sensors of fire alarms in real conditions of fire on objects - Andronov, Vladimir; Pospelov, Boris; Rybka, Evgenіy (Eastern-European Journal of Enterprise Technologies, 2016)
The theoretical analysis of the generalised circuit of the thermal sensor has shown that it is a converter of information of the resistive sensitive element into the corresponding voltage, which is carried out by the bridge measuring circuit. The dynamic model of the generalised circuit of the thermal sensor of fire alarm is presented in the form of the differential equations in the state space for the thermoresistive sensitive element in the form of a thin plate is developed on the basis of the generalised circuit of the thermal sensor. The private model of the thermal sensor of the first approximation in the state space is received for values Bi≤1. The given model allows researching the dynamic accuracy of the thermal sensor in various conditions of the fire alarm use taking into account the casual ambient temperature indignations. The influence of parameters of the bridge circuit and also of the sensitive element of the thermal sensor on dynamic accuracy in various conditions is investigated on the basis of this model. The analysis of dependence of the value of the second initial moment of an error on the considered characteristic parameters of the thermal sensor in dynamic conditions in the presence of casual temperature indignations of various intensity has shown that there are minimum values of the second initial moment of an error. Generally the minimum values of the second initial moment of an error depend on the characteristic parameters of the thermal sensor, current time and temperature conditions in the environment, characterised by the fire centre. There are possibilities of maintenance of invariance in time of the second initial moment of an error. The dependences of the optimum value of the characteristic parameter B1,1opt of the thermal sensor on speed of temperature increase caused by the fire centre, and also the intensity of masking casual temperature indignations on the object are received for this case. The received results allow to predict the expected accuracy for existing thermal sensors in various conditions of use, and also to develop optimum thermal sensors of single fire alarms for the guaranteed detection of low-power fire for real objects’ protection.